Research on Quality of Service Based Routing Protocols for Mobile Ad Hoc Networks - Selman Hizal; Ahmet Zengin (LPPM ITB, 2020)
Quality of service (QoS) based routing protocols play a significant role in MANETs to maintain proper flow of data with efficient power consumption and without data loss. However, several network resource based technical challenges or issues are encountered in the design and implementation of QoS routing protocols that perform their routing function by considering the shortest route or the lowest cost. Furthermore, a secondary route is not reserved and alternative routes are not searched unless the established route is broken. The current structures of the state-of-the-art protocols for MANETs are not appropriate for today's high bandwidth and mobility requirements. Therefore, research on new routing protocols is needed, considering energy level, coverage, location, speed, movement, and link stability instead of only shortest path and lowest cost. This paper summarizes the main characteristics of QoS-based routing protocols to facilitate researchers to design and select QoS-based routing protocols. In this study, a wide range of protocols with their characteristics were classified according to QoS routing strategy, routing information update mechanism, interaction between network and MAC layer, QoS constraints, QoS guarantee type and number of discovered routes. In addition, the protocols were compared in terms of properties, design features, challenges and QoS metrics.